Empathy and depression among a Chinese sample: The moderating role of rumination and attentional shift - Liu, Qipeng; Zhao, Xiaoyun; Liu, Weidi; Liu, Qianchen (Frontiers in Psychology, 2022)
Background Although previous studies have explored the moderating role of emotional regulation strategies in the relationship between empathy and depression, no studies have studied the moderating role of attentional control in the relationship between empathy and depression. To address this research gap, the present study investigated the moderating roles of rumination and attentional control in the relationship between empathy and depression. Methods 423 participants filled out questionnaires anonymously, including Interpersonal Reactivity Index, Attention Control Scale, Self-rating Depression Scale, and Rumination Response Scale. PROCESS macro for SPSS was used for moderating effect analysis. Results Rumination and attentional shift moderated the relationship between emotional empathy and depression. Specifically, the lower rumination or the higher attentional shift, the stronger the negative association between emotional empathy and depression. Attentional shift moderated the relationship between cognitive empathy and depression, and cognitive empathy was significantly associated with depression only among participants whose attentional shift is high. Conclusion The study showed that rumination and attentional shift play important roles in the relationship between empathy and depression. The findings implicated that the positive role of good emotional regulation strategies and executive function for individuals in the relationship between empathy and depression.